Impact of Big Five Personality on Employee Burnout: A Mediated Analysis through Psychological Empowerment - Alkharani, Ouys; Suhariadi, Fendy; Mudzakkir, Mohammad Fakhrudin (RSF Conference Series: Business, Management and Social Sciences, 2024)
Burnout has become a much-discussed mental health problem in modern society. Although burnout can occur in many professions, research in the industry sector is limited. This study aims to determine the mediating effect of Psychological Empowerment on the relationship between Big Five personality and burnout. This research combines explanatory research methods with quantitative methodology. The population of this study were all employees of PT Telkom Access, totalling 125 people. The measurements used in this study are the Big Five Inventory (BFI) scale, Burnout Assessment Scale (BAT), and Psychological Empowerment Scale. The results showed that the big five personality significantly affect burnout. Dimensions that affect burnout are conscientiousness and neuroticism, while extraversion, agreeableness, and openness to experience are not significant. The effects of extraversion, agreeableness, and openness to experience burnout were weak in this study, although many previous studies have supported the relationship between these two variables. The test results of the mediating role of Psychological Empowerment show that the dimensions of conscientiousness and openness to experience influence burnout most, followed by the dimensions of extraversion, agreeableness, and neuroticism. Thus, the mediation of psychological empowerment is proven effective in playing the big five personality relationship with burnout. This study has limitations that must be addressed. First, the model has limited work resource and demand variables as the study focuses on individual variations rather than job features. Secondly, as this study used self-reported surveys, shared method variance may be the cause of the relationship.